Prosedur Perpanjangan Safety Construction Certificate Kapal SPB. Sainty Governor oleh PT. Pasific Samudra Sentosa Bandar Lampung: Penelitian - Meriah Kita Deliani; Rio Nardi Jan Brema Nahampun (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The SPB Sainty Governor vessel operating in maritime waters is required to possess a valid Safety Construction Certificate (SCC) to ensure safe and compliant operations. Therefore, the periodic renewal of the Safety Construction Certificate is a crucial process to guarantee that the vessel continues to meet applicable safety standards. This paper provides a detailed review of the SCC renewal procedure for the SPB Sainty Governor, covering essential aspects such as the required administrative documents, stages of comprehensive inspections to assess the vessel’s physical and operational conditions, and compliance with safety standards established by both national and international maritime authorities. The objective of this study is to offer a comprehensive understanding of the SCC renewal process and to emphasize the importance of safety considerations at every stage of vessel operations. Ensuring compliance with safety regulations not only protects the crew and passengers but also contributes to environmental protection and enhances the company’s reputation within the increasingly competitive maritime industry. This study employs a literature review approach combined with field research methods to obtain accurate and relevant data related to the implementation of the Safety Construction Certificate renewal procedure.